Effects of Calcitonin-Gene-Related-Peptide on Auditory Nerve Activity - Le Prell, Colleen G.; Hughes, Larry F.; Dolan, David F.; Bledsoe, Sanford C. (Frontiers in Cell and Developmental Biology, 2021)
Calcitonin-gene-related peptide (CGRP) is a lateral olivocochlear (LOC) efferent neurotransmitter. Depression of sound-driven auditory brainstem response amplitude in CGRP-null mice suggests the potential for endogenous CGRP release to upregulate spontaneous and/or sound-driven auditory nerve (AN) activity. We chronically infused CGRP into the guinea pig cochlea and evaluated changes in AN activity as well as outer hair cell (OHC) function. The amplitude of both round window noise (a measure of ensemble spontaneous activity) and the synchronous whole-nerve response to sound (compound action potential, CAP) were enhanced. Lack of change in both onset adaptation and steady state amplitude of sound-evoked distortion product otoacoustic emission (DPOAE) responses indicated CGRP had no effect on OHCs, suggesting the origin of the observed changes was neural. Combined with results from the CGRP-null mice, these results appear to confirm that endogenous CGRP enhances auditory nerve activity when released by the LOC neurons. However, infusion of the CGRP receptor antagonist CGRP(8-37) did not reliably influence spontaneous or sound-driven AN activity, or OHC function, results that contrast with the decreased ABR amplitude measured in CGRP-null mice.